2001
DOI: 10.1046/j.0953-816x.2001.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent changes in striatal gene expression induced by long‐term l‐DOPA treatment in a rat model of Parkinson's disease

Abstract: Current knowledge of the molecular changes induced by dopamine denervation and subsequent treatment with L-DOPA is based on studies performed on relatively acute and young animal models of parkinsonism. It is highly warranted to ask how well these models simulate the state of chronic denervation and sustained L-DOPA pharmacotherapy which are typical of advanced Parkinson's disease. This study investigates the effects of time postdenervation and L-dopa treatment duration on the striatal expression of opioid pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 15 publications
4
56
0
Order By: Relevance
“…In the 6-OHDA-lesioned rat, PPE-B mRNA levels were decreased in the striatum in the untreated state, whereas chronic treatment with L-DOPA-last dose administered 2 days before deathled to an increase in PPE-B mRNA levels compared with the levels encountered in the nonparkinsonian and L-DOPA-naive parkinsonian states (Westin et al, 2001). In another study, also performed in the rat, 6-OHDA lesion did not result in a decrease in striatal PPE-B mRNA levels .…”
Section: A Preproenkephalin and Preprodynorphinmentioning
confidence: 89%
See 1 more Smart Citation
“…In the 6-OHDA-lesioned rat, PPE-B mRNA levels were decreased in the striatum in the untreated state, whereas chronic treatment with L-DOPA-last dose administered 2 days before deathled to an increase in PPE-B mRNA levels compared with the levels encountered in the nonparkinsonian and L-DOPA-naive parkinsonian states (Westin et al, 2001). In another study, also performed in the rat, 6-OHDA lesion did not result in a decrease in striatal PPE-B mRNA levels .…”
Section: A Preproenkephalin and Preprodynorphinmentioning
confidence: 89%
“…In the rat, 6-OHDA lesion increased levels of PPE-A mRNA and subsequent treatment with L-DOPA-last dose given 24 hours before death-reversed this increase (Zeng et al, 1995). In contrast, in another study in which rats were killed 2 days after last dose, chronic treatment with L-DOPA resulted in a further increase in PPE-A mRNA (Westin et al, 2001). …”
Section: A Preproenkephalin and Preprodynorphinmentioning
confidence: 94%
“…This hypothesis is supported by several observations. For example, the region showing the most pronounced microvascular alterations within the striatum is one in which striking changes in gene and protein expression (Cenci et al, 1998;Andersson et al, 1999;Westin et al, 2001;Konradi et al, 2004) and energy consumption (Konradi et al, 2004) (B. Valastro and M. A. Cenci, unpublished observations) have been documented in this rat model of L-DOPA-induced dyskinesia. Moreover, the occurrence of pronounced vascular remodeling in the EP and the SNr is compatible with the anatomical pattern of 2-deoxyglucose (2-DG) uptake in 6-OHDA-lesioned rats treated with L-DOPA, showing a marked increase in 2-DG utilization in the EP and SNr on the side ipsilateral to the lesion (Trugman and Wooten, 1986;Trugman et al, 1996).…”
mentioning
confidence: 86%
“…This nonphysiologic, discontinuous, or pulsatile stimulation of dopamine receptors leads to a variety of molecular and physiologic changes that are associated with the development of motor complications. These include a) alterations in levels of expression in striatal neurons of a variety of genes including preprodynorphin, delta fos-b, delta c-fos, and preproenkephalin, which have been observed in striatal neurons of dyskinetic rodents, primates, and patients with PD [288][289][290] ; and b) changes in neuronal firing pattern (e.g., frequency, bursts, pauses, synchronization) in basal ganglia output neurons. 266,269,291 More recently, it has been shown that levodopa treatment and the development of dyskinesia are associated with alterations in plasticity, 292 and with translocation of NR2B subunits of the NMDA receptor from a synaptic to an extrasynaptic location.…”
Section: 242mentioning
confidence: 99%